Perceptions and Experiences of Survivors of Mount Semeru Eruption in Getting Health Services during Covid-19 Pandemic - Sri Sunarti; Aurick Yudha Nagara; Atma Gunawan; Marshanda Shella Pramesta; Fifi Afifatus Zakiya; Victoria Maya Kurniawati (Fakultas Kedokteran Universitas Brawijaya, 2023)
Disaster events pose challenges for health workers in overcoming health problems in refugee camps. The eruption or hot clouds of Mount Semeru that occurred during the Covid-19 pandemic made sick survivors have to continue to receive health services, even though they were in refugee camps. Survivors' experiences in receiving health services and their illnesses varied widely. Perceptions of survivors in obtaining health services showed that most of them were well served and experienced a good referral system to higher-level hospitals. Home care was carried out by health workers to survivors after returning from refuges.